At the turning point: the Russian Orthodox Church in years of great upheavals (about new monograph by A. S. Puchenkov, V. V. Kalinovsky) - S. L. Firsov (Омский научный вестник: Серия "Общество. История. Современность")
The article analyzes the monograph by A. S. Puchenkov and V. V. Kalinovsky «Spiritual Outpost of Russia. Orthodox clergy of the Crimea in 1914–1920», dedicated to the activities of Orthodox clergy of the Crimea at a turning point in Russian history — from the beginning of the Great War to the end of the Civil War in Russia. A. S. Puchenkov and V. V. Kalinovsky, in the opinion of the reviewer, are able to competently put together both sources known to experts for a long time, and documents that they introduced into historical circulation for the first time. S. L. Firsov separately emphasizes as a positive fact that the authors paid significant attention to the study of the moral and ethical state of the Orthodox population of Crimea having examined various aspects of the influence of faith on his life. According to S. L. Firsov, A. S. Puchenkov and V. V. Kalinovsky made a worthy contribution to the study of the issue of Russian confession and the martyrs of the faith, writing an honest and sincere book, useful for everyone interested in the history of the Russian Orthodox Church of the XX century and the history of the Russian Revolution.